From Millennial to Generation Z: The State of Digital Literacy among Youths Dealing with Disinformation During Elections - Jati, Wasisto Raharjo (UI Scholars Hub, 2024)
The role of the younger generation in politics has played an important role in shaping Indonesian democracy. Since the era of the independence revolution until the post- reform era, young people have become central actors to be a guardian of democracy, especially participation in elections. Although the active role of young people is mostly carried out in various extra-parliamentary ways, such as street demonstrations, young people are now increasingly focusing on efforts to combat disinformation/misinformation in cyberspace. This stance is in line with the current development of democracy which leads to the digital world so that young people are also adaptive. The development of Indonesia's digital world directly impacts participation in contemporary elections. Following up with the various arguments previously presented, this study seeks to further elaborate on the political expression of young people in elections, particularly in educating the impact of disinformation. Furthermore, the method used is descriptive analysis by critically reviewing various previous research findings, be it publications in books, journals, or other relevant literature. The research results show that the role of young people is actually active, but differences in socio- economic and socio-demographic backgrounds are obstacles in participating actively in fighting disinformation. In addition, digital literacy, which is still unequal among young people, is also a challenge that needs to be addressed immediately in order to realize better quality Indonesian elections and democracy in general going forward